2014
DOI: 10.1186/s12989-014-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-term diesel exhaust inhalation in a controlled human crossover study is associated with changes in DNA methylation of circulating mononuclear cells in asthmatics

Abstract: BackgroundChanges in DNA methylation have been associated with traffic-related air pollution in observational studies, but the specific mechanisms and temporal dynamics therein have not been explored in a controlled study of asthmatics. In this study, we investigate short-term effects of diesel exhaust inhalation on DNA methylation levels at CpG sites across the genome in circulating blood in asthmatics.MethodsA double-blind crossover study of filtered air and diesel exhaust exposures was performed on sixteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 68 publications
0
86
0
Order By: Relevance
“…Recent studies indicate that exposure to diesel also leads to altered methylation status of TEs, suggesting the epigenetic alterations may be also involved in lung carcinogenesis. Jiang and colleagues, in their controlled human crossover study, reported that short-term diesel exhaust inhalation was associated with changes in DNA methylation of circulating mononuclear cells in 16 asthmatics 6 and 30 hours postexposure [150]. Similar to the findings in RAW264.7 macrophages [142], the response to diesel exhaust exposure within L1 and Alu elements was not uniform, with sites of both hypo- and hypermethylation being identified [150].…”
Section: Transposable Elements and Environmental Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that exposure to diesel also leads to altered methylation status of TEs, suggesting the epigenetic alterations may be also involved in lung carcinogenesis. Jiang and colleagues, in their controlled human crossover study, reported that short-term diesel exhaust inhalation was associated with changes in DNA methylation of circulating mononuclear cells in 16 asthmatics 6 and 30 hours postexposure [150]. Similar to the findings in RAW264.7 macrophages [142], the response to diesel exhaust exposure within L1 and Alu elements was not uniform, with sites of both hypo- and hypermethylation being identified [150].…”
Section: Transposable Elements and Environmental Contaminantsmentioning
confidence: 99%
“…Jiang and colleagues, in their controlled human crossover study, reported that short-term diesel exhaust inhalation was associated with changes in DNA methylation of circulating mononuclear cells in 16 asthmatics 6 and 30 hours postexposure [150]. Similar to the findings in RAW264.7 macrophages [142], the response to diesel exhaust exposure within L1 and Alu elements was not uniform, with sites of both hypo- and hypermethylation being identified [150]. Specifically, out of the 31 L1differentially methylated positions in the genome, 13 increased, while 18 decreased in DNA methylation after exposure.…”
Section: Transposable Elements and Environmental Contaminantsmentioning
confidence: 99%
“…Short-term diesel exhaust exposure (DEP), as a model of particulate air pollution, was next investigated for association with DNA methylation differences in blood samples from 16 19-to 35-year-old nonsmokers with asthma and/or airway hyper-responsiveness using linear mixed effects modeling to compare post-DEP versus pre-DEP, and postfiltered air particles versus prefiltered air particles (35). Adjustment was done using a 5% Benjamini and Hochberg false discovery rate-correction for multiple testing on the set of probes selected for the analysis.…”
Section: Dna Methylation In Relation To Longand Short-term Air Pollutmentioning
confidence: 99%
“…As a marker for short-term, trafficrelated air pollution exposure, 16 adult nonsmokers with asthma were exposed to 2 hours of DEP, at an average concentration of 300 mg/m 3 , containing high levels of NO 2 (0.22 ppm) (35,37). The difference in DNA methylation level was tested in blood samples pre-exposure versus postexposure.…”
mentioning
confidence: 99%
“…Emerging evidence suggests that, amongst various ethnic groups, certain epigenetic regulatory pathways respond differentially to exposure to known environmental toxins (66)(67)(68). The causal link between tobacco inhalation, the toxin most commonly associated with lung cancer development, and gene promoter methylation has been explored within the context of ethnicity and resulted in inconsistent findings.…”
Section: Differences In Response To Environmental Toxinsmentioning
confidence: 99%